Analysis of stochastic technical trading algorithms - Markus Höchstötter; Mher M. Safarian; Anna Krumetsadik (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
We apply the well-known CUSUM, the Girshick-Rubin, the Graversen-Peskir- Shiryaev and an improved alteration of the Brodsky-Darkovsky algorithm as trading strategies involving only mutually exclusive long positions in cash and the DAX at Xetra intraday auction prices. We select optimal pairs of fixed thresholds for up- and downmovements from a pre-defined two-dimensional grid, hence, admitting asymmetric intervals. We show that under three different scenarios for transaction costs, the improved Brodsky-Darkovsky technique not only outperforms the passive investment in the DAX but also the other three presented algorithms.
urn:nbn:de:swb:90-554293
Keywords: 330; CUSUM; Girshick-Rubin; Graversen-Peskir-Shiryaev; Brodsky-Darkovsky; trading algorithm; DAX